Birefringence and Hidden Photons - Gamboa-Rios, J (World Scientific Publishing Co. Pte Ltd, 2018)
We study a model where photons interact with hidden photons and millicharged particles through a kinetic mixing term. Particularly, we focus on vacuum birefringence effects and we find a bound for the millicharged parameter assuming that hidden photons are a piece of the local dark matter density. © World Scientific Publishing Company.